Case Report: Surgery and genetic analysis of a complete androgen insensitivity syndrome family with testicular malignant tumors - Jiang, Lu; Jia, Peng; Duan, Baofeng; Zhang, Yan (Frontiers in Genetics, 2023)
Introduction: Complete androgen insensitivity syndrome (CAIS) is a rare sex development disorder that results from X-linked androgen receptor gene mutations. Malignant transformation of the gonads is the most feared complication in postpubertal patients. Methods: In the current report, primary amenorrhea, infertility, and groin mass were symptoms described by a 58-year-old woman and his younger sister. Their two aunts, who shared the same clinical traits, passed away for an unknown reason. Results: After gonadectomy, both patients were diagnosed with seminoma and an extratesticular benign tumor, and the elder sister suffered from breast cancer about a year after the operation. The diagnosis of CAIS was verified by whole-exome sequencing (WES), in which an uncommon mutation (c.2197G>A) in the AR gene was identified. Discussion: This is the first family report of CAIS with germ cell tumors. The identified AR gene mutation based on WES can expand the understanding of CAIS.